Development of a Modified East-West Interface for Distributed Control Plane Network - Adedokun, E. A.; Adekale, A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
The East-West Interface is important in achieving communication in a distributed control plane network such as a Wide Area Network (WAN); to enable scalability and distribution of the control plane. In this paper, a Modified Communication Interface for Distributed Control Plane (mCIDC) was developed to ensure communication in WANs. The mCIDC interface allows the synchronization of different modules in the controller to enable consistent high availability and efficient communication among controllers in the East-West Interface needed for Software Defined Network (SDN) to scale in a WAN environment. The modified-CIDC (mCIDC) is developed based on the Communication Interface for Distributed Control Plane (CIDC) and implemented on top of Floodlight Controller using the ISyncService module. The performance of the mCIDC and CIDC was compared using captured Transmission Control Protocol (TCP) packets, TCP errors and inter-controller communication overload (ICO). The results indicated that for Claranet_2; mCIDC showed a better performance in minimizing number of Captured TCP Packets, TCP Errors and ICO by 26.55%, 17.89%, and 19.35% respectively when compared with CIDC, while for Claranet_3; 15.82%, 21.60% and 29.25%   for Captured TCP Packets, TCP Errors and ICO respectively, when compared with CIDC. This shows that the mCIDC ensures communication by transmitting the necessary required packets (information) among controllers with reduced TCP errors and fewer overloads.